#TITLE_ALTERNATIVE# - FRANS SATRIO (NIM : 12106025); Pembimbing :Dr. Rudianto Ekawan, ST., MT, RULY
and a mine life. It provides the minimum average grade of the ore reserves below which the mining is uneconomic or the grade at which all the mining costs are recovered and no profit left. That is the COG that determines the mining edges, ore reserves, and if mixing/blending is necessary. It becomes more critical when calculating the COG of a metal mine since there are many factors that must be taken into account. In this research, the COG of an underground cut-and-fill gold mine operated by PT. Antam Tbk. UBPE Pongkor has been successfully performed for the period of January-December 2009. The COG was calculated by the means of methodology and concept demonstrated in two literatures authored by Kenneth F. Lane “The Economic Definition of Ore" in 1988 (Lane's Model) and Jean-Michael Rendu "An Introduction to Cut-Off Grade Estimation” in 1998 (Rendu's Model). Later on, the COGs obtained from the two models were compared with methodology and concept COG from PT. Antam Tbk. UBPE Pongkor (Antam's Model). Having performed the calculation, it was shown that Antam's Model provided smaller COG than that of Lane's and Rendu's Model. Antam's Model showed COG equivalent of 3.38 g/ton, while Lane's Model and Rendu's Model showed COG of 4.18 and 4.11 g/ton, respectively. It can be seen that Rendu's Model provides a better COG value. This means that Rendu's Model, where all the costs classified as the expenses contributing to the COG are the direct costs that is significantly related to the mine operation, may provide a more meaningful methodology and concept for COG calculation. However, it should be noted that the concept calculation of equivalent grade must be applied in Antam’s Model since silver (Ag), in comparatively high grade, has been known to exist as the gangue mineral within their main ore (Au). When this gangue mineral can be separated from the main ore and sold to markets, this will benefit the company even more. Therefore, Rendu's Model was then modified in order to put the existence of this gangue mineral into account. Having modified Rendu's Model, it was shown that the COG equivalent for the same period was only 3.72 g/ton. This means that the existence of silver as the gangue mineral in the ore may significantly decrease the COG of the mine. The decrease can be quantified by knowing the percentage of the grade of Ag to Au.